2017
DOI: 10.1177/0145561320919603
|View full text |Cite
|
Sign up to set email alerts
|

5-HT7 receptorsare over-expressed in patients with nasal polyps

Abstract: Nasal polyposis (NP) is an inflammatory disease of the paranasal sinuses and nasal cavity. The primary purpose of our study is to determine the expression of 5-HT7 receptors both in nasal polyps and in healthy tissue in the nasal cavity. The subsequent aim is to compare the expression of 5-HT7 receptors in patients with NP and in inferior turbinate tissue (control).The study included 60 participants (40 with NP and 20 controls) aged 35 to 62 years. Nasal polyp samples were collected from all patients and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The 5-HT7 receptors were mainly discovered in the central nervous system, 59 but subsequently, the peripheral effects were also frequently investigated. 60,61 However, no study thus far has investigated the pre-and post-injury levels of 5-HT7 receptors in cardiac tissue. In our study, we examined the presence of 5-HT7 receptors in heart tissue in rats that were fed with HFD, followed by ISO and MI models and the damage-dependent alteration of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT7 receptors were mainly discovered in the central nervous system, 59 but subsequently, the peripheral effects were also frequently investigated. 60,61 However, no study thus far has investigated the pre-and post-injury levels of 5-HT7 receptors in cardiac tissue. In our study, we examined the presence of 5-HT7 receptors in heart tissue in rats that were fed with HFD, followed by ISO and MI models and the damage-dependent alteration of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study conducted considering the increase in serotonin in nasal polyps showed that 5-HT7 receptors are expressed in the nasal cavity, and 5-HT7 receptors are expressed at high levels in patients with nasal polyps. 75 …”
Section: Preclinical Findings About the Therapeutic Potential Of Peri...mentioning
confidence: 99%